Work-disability in low back pain patients with or without surgery, and the role of social insurance regulation changes in Sweden. (14th November 2018) - Rahman, Syed; Mittendorfer-Rutz, Ellenor; Dorner, Thomas E; Pazarlis, Konstantinos; Ropponen, Annina; Svedberg, Pia; Wang, Mo; Helgesson, Magnus
Abstract: Background: The aims were to study the differences in work-disability in patients with low back pain (LBP) in relation to (i) treatment provided (non-surgical or lumber spine surgery (decompression or fusion), and (ii) two time points, i.e. before and after the social insurance regulation changes in the in 2008. Methods: All non-pensioned individuals, aged 19–60 years, living in Sweden, diagnosed with LBP in 2004–06 or 2008–10 were included ( n = 153739). Hazard ratios (HRs) with 95% confidence intervals for long-term sickness absence (>90 days, LTSA) and disability pension (DP) for LBP-patients (non-surgical, decompression, fusion, both surgeries) were estimated by Cox regression compared with the matched references from the general population without LBP ( n = 566008). Results: LBP-patients had a higher risk of subsequent work-disability compared with the references before and after insurance regulation changes. LBP-patients receiving decompression surgery had similar risk for later work-disability as those treated non-surgically. However, following regulation changes, LBP-patients undergoing fusion surgery had higher risk estimates of both LTSA (HR: 3.3) and DP (HR: 4.8) than patients treated non-surgically (HR: LTSA 2.1; DP 2.5) or with decompression (HR: LTSA 2.6; DP 2.1). In the adjusted models, risk estimates mainly attenuated after controlling for previous sickness absence. Conclusion: Risk for subsequent work-disability among LBP-patients was higher compared with people without LBP and lumbar spine surgery. Discrepancies in risk were explained by the treatment provided previous sickness absence and changes in the social insurance regulations, specifically LBP-patients treated with fusion surgery had an increased risk of subsequent work-disability after changes in regulations.